Cardio-respiratory Fitness is Independently Associated with Cardio-Metabolic Risk Markers in Severely Obese Women - Waldburger, R.; Wilms, B.; Ernst, B.; Thurnheer, M.; Schultes, B. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Many studies have shown an inverse relationship between cardio-respiratory fitness and cardio-metabolic risk markers in normal-weight to moderately obese subjects. However, whether such a relationship exists in severely obese subjects is not known.Cardio-respiratory fitness was measured by bicycle spiroergometry in 308 severely obese women (all BMI>35 kg/m2). The following cardio-metabolic risk markers were assessed: Glycolized hemoglobin levels (HbA1c), fasting glucose, insulin, calculated HOMA index, triglycerides (TG), total, low-, high-density cholesterol (Chol, LDL; HDL), Chol/HDL-Ratio, and uric acid. Computed multiple stepwise linear regression models generally included age, weight and height as independent variables.Multiple stepwise linear regression models indicated that peak but not aerobic threshold related cardio-respiratory fitness indices were independently of age, weight and height associated with several cardio-metabolic risk markers. Specifically, maximally achieved load (Watt-peak) explained 1.4% of the variance in glucose levels (beta=−0.13; p=0.04) and 2.8% of the variance in HbA1c levels (beta=−0.18; p=0.01), while maximally achieved O2-uptake explained 3.9% of the variance in TG levels (beta=−0.20, p=0.001).Our data for the first time indicate that cardio-respiratory fitness is independently associated with cardio-metabolic risk markers in severely obese women.
Keywords: physical fitness; obesity; glucose metabolism; lipids; spiroergometry